Efektivitas Pendekatan Disiplin Positif dalam Membentuk Karakter Kedisiplinan Baik pada Peserta Didik Beragama Buddha Kelas VII di SMP Negeri 3 Gangga - Juniati; Yudi Murdana, Kadek; Mimin Nur Hayati, Rista (Jounal Nyanadassana, 2024)
The positive discipline approach is a method for educating and nurturing efforts to build positive thinking and behavior in students. By implementing the positive discipline approach, it is possible to develop good character in students. Similarly, for Buddhist students in grade VII at SMP Negeri 3 Gangga, the positive discipline approach has successfully shaped their character. This research aims to understand and describe the effectiveness of the positive discipline approach in developing good character among grade VII Buddhist students at SMP Negeri 3 Gangga. The research employs a qualitative method with a descriptive type. The data collection techniques used in this study include observation, interviews, and documentation. The data sources in this research include primary and secondary sources. The data analysis techniques employed by the researcher are data reduction, data display, verification, and conclusion drawing. The results of this research indicate that the positive discipline approach is effective in developing good character among grade VII Buddhist students at SMP Negeri 3 Gangga. This is evident from the positive thinking, behavior, and character of the students. Additionally, the good character demonstrated by the students, including responsibility, self-awareness, and discipline both within and outside the school environment, supports this effectiveness.